2020
DOI: 10.7717/peerj.10487
|View full text |Cite
|
Sign up to set email alerts
|

Foliar mycoendophytome of an endemic plant of the Mediterranean biome (Myrtus communis) reveals the dominance of basidiomycete woody saprotrophs

Abstract: The true myrtle, Myrtus communis, is a small perennial evergreen tree that occurs in Europe, Africa, and Asia with a circum-Mediterranean geographic distribution. Unfortunately, the Mediterranean Forests, where M. communis occurs, are critically endangered and are currently restricted to small fragmented areas in protected conservation units. In the present work, we performed, for the first time, a metabarcoding study on the spatial variation of fungal community structure in the foliar endophytome of this ende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 78 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…Abdel-Wahab et al [40] also used metagenomics to determine the fungal diversity from five decaying leaf samples of Halophila stipulacea and found that the percentage occurrence of Basidiomycota ranged from 37.2 to 51.6%. Interestingly, the highest percentage of basidiomycetous endophytes was reported from leaves of Myrtus communis by Vas et al [45]: out of 44 OTUs generated by sequencing, 37 OTUs belonged to 12 orders of Basidiomycota (84% occurrence). Note: ND = No data.…”
Section: Basidiomycetous Endophytesmentioning
confidence: 95%
See 3 more Smart Citations
“…Abdel-Wahab et al [40] also used metagenomics to determine the fungal diversity from five decaying leaf samples of Halophila stipulacea and found that the percentage occurrence of Basidiomycota ranged from 37.2 to 51.6%. Interestingly, the highest percentage of basidiomycetous endophytes was reported from leaves of Myrtus communis by Vas et al [45]: out of 44 OTUs generated by sequencing, 37 OTUs belonged to 12 orders of Basidiomycota (84% occurrence). Note: ND = No data.…”
Section: Basidiomycetous Endophytesmentioning
confidence: 95%
“…Table 2 documents endophytic Basidiomycota from a review of 25 selected publications from a wide range of host plants and plant parts, and from temperate to tropical geographical locations, with identifications based on morphology or a combination of morphology and sequence data, yielding 85 species in 46 genera. Two publications document the detection of endophytes in Myrtus communis and decaying leaves of Halophila stipulacea by high-throughput sequencing (metagenomics) (culture-independent method, CID) [40,45], while 23 publications identify the endophytes by isolation and morphological procedures (culture-dependent method, CD).…”
Section: Basidiomycetous Endophytesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a broader interpretation of a lifestyle that has recently been termed viaphytism (Nelson et al 2020 ), certain decomposing fungi can use as endophytes organs of the plant host as a refuge to overcome periods of own environmental stress. For example, such species may exist as temporary foliar endophytes to then enhance their own spread by leaf and needle fall to the forest floor providing more versatile woody substrates to them for saprotrophic hyphal growth (Nelson et al 2020 ; Vaz et al 2020 ). Functions of still other endophytes remain elusive (Gehring et al 2020 ; Rodriguez et al 2009 ), or may they simply be commensals nurtured by a host without recognizable impacts on their feeder (Langer et al 2021 ; Terhonen et al 2019 ; Zanne et al 2020 )?…”
Section: Fungal Communities Associated With Treesmentioning
confidence: 99%